Blood group-specific apheresis in combination with daratumumab as a rescue therapy of acute antibody-mediated rejection in a case of ABO- and human leukocyte antigen-incompatible kidney transplantation - Süsal, Can C.; Kraft, Leonie; Ender, Andrea; Süsal, Caner; Schwenger, Amelie; Amann, Kerstin Ute; Böhmig, Georg A.; Schwenger, Vedat (SAGE Open Medical Case Reports, 2023)
We report a case of antibody-mediated rejection treated with the human CD38 monoclonal antibody daratumumab in a 58-year-old female patient with end-stage kidney disease due to autosomal dominant polycystic kidney disease who received an ABO- and human leukocyte antigen antibody-incompatible living donor kidney transplant. The patient experienced an episode of severe antibody-mediated rejection within the first week of transplantation. Blood-group-antibody selective immunoadsorption in combination with administration of four doses of daratumumab (each 1800 mg s.c.) led to a persistent decrease of ABO- and more interestingly donor-specific human leukocyte antigen antibody reactivity and resulted in clinical and histopathological remission with full recovery of graft function, which has remained stable until post-transplant day 212. This case illustrates the potential of targeting CD38 in antibody-mediated rejection.
CRIS-Team Scopus Importer:2023-11-24
Keywords: antibody-mediated rejection; blood-group incompatibility; Case report; daratumumab; HLA incompatibility; kidney transplantation; living-donor transplantation; rejection therapy